2022
DOI: 10.3390/ijms23063331
|View full text |Cite
|
Sign up to set email alerts
|

Nimodipine Exerts Time-Dependent Neuroprotective Effect after Excitotoxical Damage in Organotypic Slice Cultures

Abstract: During injuries in the central nervous system, intrinsic protective processes become activated. However, cellular reactions, especially those of glia cells, are frequently unsatisfactory, and further exogenous protective mechanisms are necessary. Nimodipine, a lipophilic L-type calcium channel blocking agent is clinically used in the treatment of aneurysmal subarachnoid haemorrhage with neuroprotective effects in different models. Direct effects of nimodipine on neurons amongst others were observed in the hipp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“… 44 It is therefore noteworthy that apart from reducing blood pressure, nimodipine is directly protective to neurons, 16 and anti-inflammatory effects in reducing astrocyte and microglial activation, 16 with protective effects on pericytes and oligodendrocytes. 16 , 45 Even in vitro, where effects on blood flow are not involved, nimodipine still shows cell type–independent suppression of stress-dependent apoptosis, 46 and protection of tissue slices 47 and the neurovascular unit. 48 In summary, it is likely that the mechanisms underlying the neuroprotective effects of nimodipine are multifactorial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 44 It is therefore noteworthy that apart from reducing blood pressure, nimodipine is directly protective to neurons, 16 and anti-inflammatory effects in reducing astrocyte and microglial activation, 16 with protective effects on pericytes and oligodendrocytes. 16 , 45 Even in vitro, where effects on blood flow are not involved, nimodipine still shows cell type–independent suppression of stress-dependent apoptosis, 46 and protection of tissue slices 47 and the neurovascular unit. 48 In summary, it is likely that the mechanisms underlying the neuroprotective effects of nimodipine are multifactorial.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it appears that nimodipine has particular benefits that are not necessarily shared by other dihydropyridine calcium channel–blocking agents. 47 Thus, the protective effects of nimodipine are not adequately reproduced by nifedipine in slice cultures, 49 or by nicardipine in a systematic review. 50 Indeed, although nimodipine is used to improve outcome in subarachnoid hemorrhage on the basis that it avoids delayed vasoconstriction, the actual mechanism of action is now being re-evaluated since other interventions that successfully target angiographic vasospasm have not improved outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Nimodipine is a lipophilic L-type calcium channel blocker and a potent cerebral vasodilator. Hohmann et al [ 6 ] investigated the neuroprotective effect of nimodipine on excitotoxic injuries in organotypic hippocampal slice cultures (OHSCs) and found that nimodipine reduced the impact of the injury in OHSCs when they were co-applied with NMDA, indicating the neuroprotective effect on excitotoxic injuries in the hippocampus.…”
mentioning
confidence: 99%